Chapter Other Criteria. Problematic Nudes - Méndez Baiges, Maite (Studi e saggi, 2022)
In the 1960s and 1970s this formalist version seen in the previous chapter began to show signs of fatigue. Some critics and art historians began to show interest in the personages on stage in Les Demoiselles. Early on John Nash linked the damsel squatting at lower right of the canvas with the myth of Medusa. Leo Steinberg immediately formulated a series of questions that constituted a direct attack against the formalist version. Why should we examine a painting that presented five naked prostitutes, all gazing fixedly at the viewer, merely from the formalist perspective? The time had come to take into account the content of the painting and consequently all of modern art which had been restricted by the prevailing formalism. This chapter tells how the formalist arguments were refuted and cleared the way for the iconological studies that placed the powerful sexual content in the foreground. The person mainly responsible for this was Leo Steinberg who sparked off an authentic revolution on the way to deal with this work and Modernism as a whole.